Presence of Legionella spp. in cooling towers: the role of microbial diversity, Pseudomonas, and continuous chlorine application. (1st February 2020) - Paranjape, Kiran; Bédard, Émilie; Whyte, Lyle G.; Ronholm, Jennifer; Prévost, Michèle; Faucher, Sébastien P.
Abstract: Legionnaires' disease (LD) is a severe pneumonia caused by several species of the genus Legionella, most frequently by Legionella pneumophila . Cooling towers are the most common source for large community-associated outbreaks. Colonization, survival, and proliferation of L. pneumophila in cooling towers are necessary for outbreaks to occur. These steps are affected by the chemical and physical parameters of the cooling tower environment. We hypothesize that the bacterial community residing in the cooling tower could also affect the presence of L. pneumophila . A 16S rRNA gene targeted amplicon sequencing approach was used to study the bacterial community of cooling towers and its relationship with the Legionella spp. and L. pneumophila communities. The results indicated that the water source shaped the bacterial community of cooling towers. Several taxa were enriched and positively correlated with Legionella spp. and L. pneumophila . In contrast, Pseudomonas showed a strong negative correlation with Legionella spp. and several other genera. Most importantly, continuous chlorine application reduced microbial diversity and promoted the presence of Pseudomonas creating a non-permissive environment for Legionella spp. This suggests that disinfection strategies as well as the resident microbial population influences the ability of Legionella spp. to colonize cooling towers. Graphical abstract: Image 1 Highlights: The bacterial community profiles of 18 cooling towers were characterized. The bacterial communities are influenced by the source of the makeup water. The presence of Legionella is positively correlated with alpha diversity. Legionella is negatively correlated with Pseudomonas. Continuous chlorine treatment restricts Legionella but promotes Pseudomonas .